2017
DOI: 10.1093/cid/cix853
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Multidrug-Resistant Mycoplasma genitalium in Human Immunodeficiency Virus-Infected Men Who Have Sex With Men in Alabama

Abstract: We tested for Mycoplasma genitalium in 157 HIV-infected men. Urogenital and rectal prevalence were 10.8% and 6.4%. Macrolide resistance mutations were detected in 70.6% and 80% of urogenital and rectal samples, and fluoroquinolone resistance mutations in 26.7% and 40%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
48
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 12 publications
7
48
4
1
Order By: Relevance
“…With the exception of a study from Greenland, the mutation frequency (66.4%) [62] observed was higher than frequencies reported by Russia and Estonia (0.7 10%) [63], South Africa (10%) [64], southern Sweden (13%) [65], France (17%) [66], Japan (42.2%) [42], southern USA (48%) [67], Norway (56%) [68], and Denmark (57%) [68]. However, our rate of 66.4% is lower than rates reported from England (82.4%) [69], the US (Alabama: 74.1% HIV positive MSM) [26], and Australia (79.4%) [70].…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…With the exception of a study from Greenland, the mutation frequency (66.4%) [62] observed was higher than frequencies reported by Russia and Estonia (0.7 10%) [63], South Africa (10%) [64], southern Sweden (13%) [65], France (17%) [66], Japan (42.2%) [42], southern USA (48%) [67], Norway (56%) [68], and Denmark (57%) [68]. However, our rate of 66.4% is lower than rates reported from England (82.4%) [69], the US (Alabama: 74.1% HIV positive MSM) [26], and Australia (79.4%) [70].…”
Section: Discussioncontrasting
confidence: 59%
“…NC_000908.2) was used as a reference strain. Amino acid changes in the QRDRs of the gyrA and parC genes in this study were compared with previous studies [6,24,26,33,38,41].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In our study, 60% and 30% of 20 strains showed mutations associated with macrolide and quinolone resistance, and 25% with both. Prevalence of macrolide resistance of M. genitalium may now exceed 50% [3,24] and is reported to be even higher in HIV-positive patients [25] or HIV-PrEP users [26,27], which corresponds to our results. The study from Germany calculated a rate of 80% macrolide-resistant strains [22].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, there is a growing consensus from research in China and internationally, of other characteristics contributing to increased risk of M. genitalium infections. Characteristics linked to increased infection include experiencing problems with fertility for both men [9,30] and women [31], abnormal pregnancy status [32], and from being members of vulnerable populations, including menwho-have-sex-with men (MSM) [33], female sex workers (FSW) [34], and people living with HIV [35].…”
mentioning
confidence: 99%